AN ERROR ANALYSIS OF THE USE OF PREPOSITIONS IN STUDENT’S DESCRIPTIVE TEXT IN WRITING OF THE EIGHTH YEAR STUDENTS IN MTS SWASTA AL-JUMHURIY AH SEI ROTAN - NURHAMIDAH, RISKA NURHAMIDAH (Faculty of Tarbiyah nad Teacher Training, 2022)
The objective of this research is to identify the types of students error in using prepositional place in descriptive text that made by eight grade students of MTS Swasta Al-Jumhuriyah Seirotan, to identify the cause of students make error in using prepositional place. That most of students did not pay attention about using prepositional correctly in sentence.This research is qualitative research. The object of research show there are four types error made by students, omission, addition, misordering, and misformation. Based on the data, the frequency of student’s error in using prepositional place is mostly occurred in prepositional in place in with 35 errors. The second is prepositional on with 14 errors. The third is prepositional place at with 12 errors.